Kepengurusan Santri sebagai Tata Kelola Pendidikan dan Pembentukan Kepemimpinan di Pesantren Tahfiz: Studi Kasus di Pondok Pesantren Roudhotu Huffazil Qur’an Geger Madiun - Maulidi Mashadi, Hudeya Ardhy; Isthifaiyah, Arjuni Niswatil; Rohmah, Aulia Ainur; Wulan Astuti, Fika Karomah Intan Purnama; Khoiroh, Ila Sari'un (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study analyzes santri management as a mechanism of educational governance and leadership formation within the daily life of a Qur’an-memorization pesantren. It responds to the limitations of existing studies on pesantren management, which have tended to place the kiai, supervisors, curriculum, and formal institutional structures at the center of analysis, while the role of santri as actors in everyday governance remains underexplored empirically. Methods – This study employed a qualitative case study design at Pondok Pesantren Roudhotu Huffazil Qur’an, Geger Madiun. Data were collected through semi-structured interviews, observations of santri organizational activities, and institutional documentation. The data were analyzed through data condensation, thematic coding, data display, and conclusion drawing. Source and technique triangulation were used to strengthen the credibility of the findings. Findings – The findings show that santri management operates as a form of peer-authority-based governance through the division of responsibilities across security, cleanliness, education, and worship affairs; planning meetings; program coordination; supervisor guidance; and routine evaluation. However, its effectiveness remains limited because student administrators experience role conflict as both santri and organizational actors. The main challenges include unstable discipline among administrators, non-procedural communication among management members, the density of pesantren activities, and inconsistent firmness in enforcing rules. This study argues that santri management is not merely an administrative apparatus but an organizational learning space that develops responsibility, communication, collective discipline, and leadership. The article contributes to the conceptual development of pesantren governance by proposing peer-authority-based governance under supervisor guidance. Practically, pesantren need to strengthen leadership training, task guidelines for each division, coordination documentation, and follow-up evaluation so that santri management becomes more accountable, participatory, and relevant to improving the quality of Islamic boarding education. Such efforts are particularly important in pesantren contexts that emphasize discipline, moral exemplarity, and the continuous habituation of collective values through a systematic and organizational learning-oriented approach.